Status of ICT Use in Government and Non-Government Schools of Surkhet District - Acharya , Gobinda Prasad; Subedi, Rameshor (Intellectual Inception: A Multidisciplinary Research Journal of Bhojpur Campus, 2025)
The study investigates the status of ICT (Information and Communication Technology) use in government and non-government secondary schools in Surkhet district, Nepal. Despite efforts to integrate ICT into education policies, significant disparities persist in access, infrastructure and implementation. The research employs a quantitative approach, utilizing surveys and statistical analyses to explore the level of ICT usage among students, factors influencing ICT integration and students’ perceptions. Findings reveal moderate positive correlations between ICT use and variables such as access to personal devices, digital literacy, access to school ICT resources and ICT integration in the curriculum. However, students demonstrate low levels of ICT usage at school, contrasting with higher home usage. Gender differences also emerge, with females exhibiting greater confidence in ICT usage. The study underscores the need for tailored strategies to enhance ICT utilization in education, including comprehensive teacher training programs and the development of a structured ICT policy framework.